2021
DOI: 10.1111/spc3.12603
|View full text |Cite
|
Sign up to set email alerts
|

Virtual relationships: Anthropomorphism in the digital age

Abstract: For most of human history we have ascribed human‐like capacities to other entities (anthropomorphism). Recently, the digital age has created new entities: virtual agents (VAs). Increasingly, these virtual entities are complex and human‐like, specifically designed to elicit anthropomorphism from their owners and users. We employ social psychological research and theory to review how, why, and when people come to anthropomorphize VAs. Moving beyond static representations, we examine the dynamics of human‐VA rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…For example, women with high attachment avoidance or high attachment anxiety-the degree to which individuals are uncomfortable with intimacy and the degree to which individuals worry about their close relationships, respectively (Mikulincer & Shaver, 2016)-tend to anthropomorphize objects more than less avoidantly or anxiously attached women (Neave, Tyson, McInnes, & Hamilton, 2016). This prior work has focused on the factors which lead people to anthropomorphize, such as sociality motivations, and neglected the potential role of anthropomorphism in helping us form relationships (see Koike & Loughnan, 2021). We propose that once anthropomorphism begins, it may help us build a deeper relationship with non-human entities (see also Kwok, Grisham & Norberg, 2018).…”
Section: Anthropomorphism and Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, women with high attachment avoidance or high attachment anxiety-the degree to which individuals are uncomfortable with intimacy and the degree to which individuals worry about their close relationships, respectively (Mikulincer & Shaver, 2016)-tend to anthropomorphize objects more than less avoidantly or anxiously attached women (Neave, Tyson, McInnes, & Hamilton, 2016). This prior work has focused on the factors which lead people to anthropomorphize, such as sociality motivations, and neglected the potential role of anthropomorphism in helping us form relationships (see Koike & Loughnan, 2021). We propose that once anthropomorphism begins, it may help us build a deeper relationship with non-human entities (see also Kwok, Grisham & Norberg, 2018).…”
Section: Anthropomorphism and Relationshipsmentioning
confidence: 99%
“…Alexa, Cortana, Siri), virtual agents are increasingly common. To date, virtual agents have been primarily developed to replace human labour; however, as these agents increase in complexity, they are moving into other, more social domains (for a review, see Koike & Loughnan, 2021). Our romantic lives reflect one such important social domain witnessing the growing involvement of virtual agents.…”
Section: Introductionmentioning
confidence: 99%
“…A prior study showed that anthropomorphism significantly impacts user privacy concerns in the context of communicating with virtual assistants such as Apple Siri and Google Assistant on mobile devices (Ha et al, 2021). In a previous study regarding building virtual relationships, it was also argued that people could feel comfort and security if virtual agents are perceived as anthropomorphized (Koike and Loughnan, 2021). Therefore, anthropomorphism is inferred to have a positive effect on perceived security in the current study context.…”
Section: Anthropomorphism and User Perceptionsmentioning
confidence: 75%
“…Anthropomorphism can be defined as “the attribution of distinctively human-like feelings, mental states, and behavioral characteristics to inanimate objects, animals, and in general to natural phenomena and supernatural entities” ( Salles et al, 2020 , p. 89). However, Koike and Loughnan (2021) acknowledge the limitation of the current social psychology models in addressing the complexities of our relations with virtual agents. Similarly, Gambino et al (2020) propose an extension of “computers are social actors framework” (CASA) to account for the recent changes in the interaction of people and technologies.…”
Section: Literature Reviewmentioning
confidence: 99%